Pengaruh Digital Marketing, Kualitas Produk, dan Citra Merek Terhadap Keputusan Pembelian Produk Vicenza Pasticcino - Anre; Nainggolan, Nora Pitri (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study aims to analyze the effect of digital marketing, product quality, and brand image on purchasing decisions for Vicenza Pasticcino products. The research adopts a quantitative approach with an explanatory research design. Data were collected from 100 respondents who are consumers of Vicenza Pasticcino, selected using a purposive sampling technique. Data collection was conducted through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, the data were examined through validity and reliability tests, as well as classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results indicate that digital marketing, product quality, and brand image have a positive and significant effect on purchasing decisions. Partially, digital marketing has the most dominant influence on purchasing decisions, followed by product quality and brand image. Simultaneously, the three independent variables explain 70% of the variance in consumer purchasing decisions. These findings indicate that effective digital marketing strategies, consistent product quality that meets consumer expectations, and a positive and trustworthy brand image play an important role in increasing purchase intention, consumer satisfaction, and loyalty toward Vicenza Pasticcino products.